The Impact of Technology on Family Communication - Romi Syahril; P. Priatna; Azhar Hutomo; Sri Wulandari (Manunggal Halim Jaya, 2024)
This study aims to explore the impact of technology on family communication patterns using the Family Communication Patterns Theory approach. Technology, especially digital devices such as mobile phones and social media, has changed the way families communicate, both positively and negatively. This study uses a qualitative method with a case study approach in five families in an urban area to understand how technology affects interpersonal relationships between family members. The results show that families with a high conversation orientation tend to use technology to strengthen emotional connectedness, while families with a high conformity orientation are more cautious in using technology, because they are worried about its impact on traditional values and parental control. Technology is also found to play a role in resolving family conflicts, but in some cases, it causes technoference or disruption in face-to-face communication. In conclusion, technology provides opportunities and challenges in maintaining family relationships, and its use needs to be regulated wisely to avoid negative impacts. This study suggests that families should be more aware of the limitations of technology use and prioritize direct interaction to maintain the quality of interpersonal communication.